Improving Psychological and Educational Support of University Students with Disabilities in Kazakhstan - Rakhila Aubakirova; Aisulu Zhomartova; Murshida Nurgaliyeva; Gulmira Tulekova; Gulnar Tursungozhinova; Marina Skiba; Alma Turganbayeva; Oxana Belenko (Qubahan Academic Journal, 2025)
Inclusive education in Kazakhstan faces challenges, as many institutions lack the necessary infrastructure, trained personnel, and resources to fully support students with disabilities. These barriers hinder the professional development of such students, highlighting the need for improved educational practices and support systems. The study aimed to investigate the psychological and pedagogical conditions for the effective education process of students with disabilities (SWD) as well as to examine the definite features of psychological and pedagogical support for SWD. The paper employed quasi experimental methods, surveys among the students with disabilities and comparative analysis of specialized scholarly literature. The quasi-experiment was conducted among two groups: the first group students trained in special classrooms by teachers who had studied foreign experience and had been trained to master the competencies of creating psychological and pedagogical conditions to support SWD, and the second control group of the students studying without special conditions with teachers who had not been trained abroad. As a result, we have identified the primary forms and methods of inclusive education skills training. To add more, we have summarized the experience of creating psychological and pedagogical conditions to support SWD in their professional development. The key psychological support mechanisms for SWD were determined, including psychological diagnostics, psychological counseling, group activities, and psychological and pedagogical support. We have offered summarized suggestions for teaching SWD, covering the adaptation of teaching material, expanding the range of audiovisual aids, and providing psychological support to participants in the educational process.